The Utilization of PPKn Laboratory for Increasing Social Environmental Awareness of Students in Unsyiah Labortorium High School - Rusli Yusuf; Sanusi Sanusi; Nadia Tiara Putri; Iwan Fajri (JED (Jurnal Etika Demokrasi), 2020)
Abstract. The purpose of research it is To find out how the process of utilization of the laboratory in the eyes of subjects Civics by students SMA Laboratory Unsyiah, To determine whether the use of the laboratory in the eyes of subjects PPKn will increase awareness neighborhood social students and To know is there any factor inhibiting the use of the laboratory in the eyes of subjects PPKn . This study uses a qualitative approach to the type of descriptive research. Data collection techniques in the form of observation, interviews, and documentation. The selection of a qualitative approach is in accordance with what you want to achieve in this study. Mechanical analysis of the data in the study of qualitative which consists of a reduction of data, presentation of data and draw conclusions. Results of the study showed that (1) The process of utilization of laboratory carried out by conformity with the contents of KD or materials of learning that relate to the laboratory, (2) With the use of laboratory showed that students have a sense of the level of concern for the environment social were quite good, and (3) Constraints are encountered in the use of laboratories there are four names, in the form of time, cost, transportation and permit. Then expected to the school in order to overcome the obstacles were encountered in the use of the laboratory, and the teacher’s eyes lessons PPKn in order to more improve further the effectiveness of the use of the laboratory so that students be well again in concern about the environment social. Teachers and school principals should carry out contextual-based learning processes to improve students' social care in the community.Keywords: Utilization Laboratory, Civics Education, Social Environmental ConcernAbstrak.  Tujuan penelitian ini adalah: Untuk mengetahui bagaimana proses pemanfaatan laboratorium pada mata pelajaran PPkn oleh siswa SMA Laboratorium Unsyiah, Untuk mengetahui apakah dengan pemanfaatan laboratorium pada mata pelajaran PPKn akan meningkatkan kepedulian lingkungan sosial siswa dan Untuk mengetahui adakah faktor penghambat dalam pemanfaatan laboratorium pada mata pelajaran PPKn. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Pemilihan pendekatan kualtitatif sesuai dengan yang ingin di capai dalam penelitian ini. Teknik pengumpulan data berupa berupa observasi, wawancara dan dokumentasi. Teknik analisis data dalam penelitian kualitatif yang terdiri dari reduksi data, penyajian data dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa (1) Proses pemanfaatan laboratorium dilakukan berdasarkan kesesuaian dengan isi KD atau materi pembelajaran yang berhubungan dengan laboratorium, (2) Dengan adanya pemanfaatan laboratorium menunjukkan bahwa siswa mempunyai rasa tingkat kepedulian lingkungan sosialnya yang cukup baik dan (3) Kendala yang dihadapi dalam pemanfaatan laboratorium ada empat yaitu, berupa waktu, biaya, transportasi dan izin. Maka diharapkan kepada pihak sekolah agar dapat mengatasi kendala yang dihadapi dalam pemanfaatan laboratorium, dan kepada guru mata pelajaran PPKn agar lebih meningkatkan lagi keefektifan pemanfaatan laboratorium agar siswa lebih baik lagi dalam kepedulian terhadap lingkungan sosialnya. Para guru dan kepala sekoal hendaknya melakukan proses pembelajaran berbasis kontekstual untuk meningkatkan kepedulian sosial siswa di lingkungan masyarakat.Kata Kunci: Pemanfaatan Laboratorium, Pendidikan Kewarganegaran, Kepedulian Lingkungan Sosial